2007
DOI: 10.1128/jvi.01345-06
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus Interactions with the Cell Membrane Studied by New Chromatic Vesicle and Cell Sensor Assays

Abstract: The potential danger of cross-species viral infection points to the significance of understanding the contributions of nonspecific membrane interactions with the viral envelope compared to receptor-mediated uptake as a factor in virus internalization and infection. We present a detailed investigation of the interactions of vaccinia virus particles with lipid bilayers and with epithelial cell membranes using newly developed chromatic biomimetic membrane assays. This analytical platform comprises vesicular parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…marcromolecules has been utilized to monitor the ligand-receptor binding events for viruses (17)(18)(19), toxins (20,21), bacteria (22,23) and antibody-receptor interactions. (24,25) Recently, nanoparticles were also applied for measuring biomolecules related to NIH biodefense program.…”
mentioning
confidence: 99%
“…marcromolecules has been utilized to monitor the ligand-receptor binding events for viruses (17)(18)(19), toxins (20,21), bacteria (22,23) and antibody-receptor interactions. (24,25) Recently, nanoparticles were also applied for measuring biomolecules related to NIH biodefense program.…”
mentioning
confidence: 99%
“…45 Interestingly, previous studies demonstrated that the entry of both VV and HSV-1 requires the participation of cholesterol/sphingomyelin domains. 46,47 We postulate that the incorporation of α-toxin in the keratinocyte membrane might change the cell plasma membrane structure and enhance formation of cholesterol/sphingomyelin domains with pores, thus leading to increased opportunity for viral entry. In addition, the protease activity of ADAM10 can be activated even by sublytic concentrations of α-toxin, leading to cleavage of E-cadherin, an important component for epithelial adherens junctions.…”
Section: Discussionmentioning
confidence: 99%
“…The use of chromatic vesicles in liquid samples for the detection of bacteria is very difficult because the vesicles are not specific and react with many chemicals, including detergents (Kolusheva et al 2000a;Kolusheva et al 2000b;Jelinek and Kolusheva 2001;Kolusheva et al 2001;Orynbayeva et al 2007;Groysman et al 2008;Sokolovski et al 2008).…”
Section: Discussionmentioning
confidence: 99%